Tetrahydropyranodiquinolin-8-amines as new, non hepatotoxic, antioxidant, and acetylcholinesterase inhibitors for Alzheimer's disease therapy - Dgachi, Youssef; Sokolov, Olga; Luzet, Vincent; Godyń, Justyna; Panek, Dawid; Bonet, Alexandre; Martin, Hélène; Iriepa, Isabel; Moraleda, Ignacio; García-Iriepa, Cristina; Janockova, Jana; Richert, Lysiane; et al. (European journal of medicinal chemistry, 2017)
Herein we report an efficient two step synthesis and biological assessment of 12 racemic tetrahydropyranodiquinolin-8-amines derivatives as antioxidant, cholinesterase inhibitors and non-hepatotoxic agents. Based on the results of the primary screening, we identified 7-(3-methoxyphenyl)-9,10,11,12-tetrahydro-7H-pyrano[2,3-b:5,6-h']diquinolin-8-amine (2h) as a particularly interesting non-hepatotoxic compound that shows moderate antioxidant activity (1.83 equiv Trolox in the ORAC assay), a non competitive inhibition of hAChE (IC50 = 0.75 ± 0.01 μM), and brain permeable as determined by the PAMPA-Blood Brain Barrier assay.
Keywords: hematoencefalická bariéra; aminochinoliny; cholinesterasové inhibitory; Aminoquinolines; Acetylcholinesterase; Blood-Brain Barrier; antioxidancia; GPI-Linked Proteins; lékové postižení jater; GPI-vázané proteiny; Humans; lidé; Alzheimer Disease; Antioxidants; Chemical and Drug Induced Liver Injury; Alzheimerova nemoc; acetylcholinesterasa; Cholinesterase Inhibitors